Encapsulation and Sustained Release of Curcumin using Superparamagnetic Silica Reservoirs - Chin, S.F.; K., Swaminathan Iyer; Saunders, Martin; Pierre, Tim G. St.; Buckley, Craig; Paskevicius, Mark; Raston, Colin L. (Wiley-VCH Verlag GmbH & Co., 2009)
For controlled release and targeted delivery of curcumin in an aqueous medium a method of encapsulating curcumin and magnetic nanoparticles inside porous silica matrix has been developed. Curcumin and superparamagnetic nanoparticles are loaded inside porous silica in a single process. The graphic shows the TEM image of microtomed sample of Fe3O4 particles surrounded by a silica matrix.